Influence Of Sensorless Control On The Noise Of Switched Reluctance Motor Drive - Alexander Petrushin; Maxim Tchavychalov (Institute of Advanced Engineering and Science, 2015)
The influence of the switched reluctance motor drive sensorless control on the level of its noise is considered. Theoretically justified the increase of noise level while sensorless SRM control. The results of switched reluctance motor noise measurement with sensorless control and control using the physical position sensor are given.